Technological advancement of sorption water purification for alcoholic beverage industry - Oliynyk, Svitlana; Prybylskyi, Vitalii; Chuprina, Natalia; Dovgun, Irina (My University, 2014)
The topicality of technological advancement of water conditioning by means of sorption water purification for alcoholic beverage industry is shown. Показано актуальність технологічного прогресу підготовки води за допомогою сорбційної очистки для лікеро-горілчаної промисловості.
Keywords: water; alcohol; carbon; purification; алкоголь; вуглець; очищення; вода; углерод; очистка; кафедра іноземних мов професійного спрямування; кафедра біотехнології продуктів бродіння і виноробства